Using Humanistic and Positive Psychology to Understand Mexican American Adolescents' Subjective Happiness. Issue 1 (April 2016) - CAVAZOS VELA, JAVIER; LENZ, A. STEPHEN; SPARROW, GREGORY SCOTT; GONZALEZ, STACEY LEE
Abstract : Mexican American adolescents (N = 131) provided perceptions of presence of meaning in life, search for meaning in life, hope, family importance, and subjective happiness. Perceptions of meaning in life and family importance were significant predictors of subjective happiness. A discussion regarding the importance of these findings and implications for counselors are provided.